Throughput-Optimal Scheduling for Cooperative Communications in Wireless Ad Hoc Networks. (14th September 2013) - Huynh, Thong; Hwang, Won-Joo; Lee, Suk-Hwan
Cooperative communications that take advantage of the broadcasting nature of wireless environments can help to increase system throughput in wireless ad hoc networks. However, the promised throughput might be lost in presence of the error transmission and the interference caused by relay transmission in cooperative communication. In this paper, we introduced the relay selection schemes that can control the interference at the relay to prevent the relay that may harm other pairs. Then, we proposed the throughput-optimal scheduling that takes into account error probability in decision and maximizes throughput, that is, the amount of packets transmitted without error in network. In addition, we derive a simple and lightweight framework to implement the proposed policy in distributed manner. The simulation results show that the proposed scheduling policy outperforms the noncooperative policy and multihop relay policy.